A Mini Review of Short Tandem Repeat (STR) as DNA Profiling Markers in Forensic Biology - Nitisara, Antonia Anindyanari Paramartastri; Purba, Laurentia Henrieta Permita Sari (Universitas PGRI Palembang, 2025)
The use of forensic biology methods plays an important role in handling criminal cases such as sexual violence, murder, and assault to enhance the quality of criminal investigation. These methods use polymorphic genetic markers such as short tandem repeat (STR) or microsatellites to identify individuals based on the DNA profile of the cell nucleus left on the evidence. STR markers are considered suitable for forensic analysis due to their ability to work with degraded DNA and the high heterozygosity, providing strong discrimination capabilities. The DNA profiling process involves collecting evidence samples, DNA extraction, PCR amplification, capillary electrophoresis, and comparison with national or international DNA databases. All processes follow standards to ensure accurate results. Challenges in STR analysis include the need for skilled analysts, protocol updates, database expansion, and ethical considerations regarding genetic data. Improvements in the forensic system will enhance law enforcement effectiveness and strengthen public trust in the future of forensic science.